MENGANGKAT KEARIFAN LOKAL RUMAH RAJA BALUNTARA DI TAKENGON ACEH TENGAH - Anna Permatasari Kamarudin; Sahri Adha; Maharani; Sarma Julita; Amna (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Cultural heritage relics in an area are historical evidence that need to be maintained and preserved. The cultural reserve found in Toweren Uken in the form of the traditional house of King Baluntara (wilderness). Its existence provided information regarding the formation of kingdom in the 18th century in Central Aceh. The king’s residence is a house on stilts decorated with several typical Gayo openwork ornament. Inside it is built with seven rooms with various functions which known as Umah Edet Pitu Ruang. Apart the traditional house, the village has a very diverse natural potential. It is located among Birah Panyang mountain with beautiful scenery. It has Flora, in the form of coffee plantations, rice fields and another plants. It has fauna, in the form of lake area that becomes the habitat of many types of fish and aquatic animal. The village surrounding that still traditional has potential to become a tourism of village. However, the village still needs further exploration with the stakeholder, village official and the community. Promotion is one way to make this cultural heritage known in a wider community nationally and internationally